2017
DOI: 10.4166/kjg.2017.69.6.333
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Patients with Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) includes a wide spectrum of diseases that range from simple steatosis to non-alcoholic steatohepatitis (NASH) and cirrhosis. In addition, the burden of NAFLD is rapidly growing. Previously, NAFLD was regarded as a hepatic manifestation of metabolic syndrome, which is a traditional cardiovascular disease (CVD) risk factor. However, there has been an increasing evidence that suggest NAFLD to be an independent risk factor of CVD. Therefore, currently, NAFLD should be reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Therefore, changes in liver and serum lipid parameters can be a predictor of disease development. 24 Kantartzis et al 25 in their study on 16 patients with fatty liver and 24 control subjects found that fatty liver was associated with decreased levels of high-density lipoprotein 2 (HDL 2 ) which is potent antiatherogenic. Moreover, in patients with NAFLD, abnormal serum ALT and AST are usually present when the disease progress to steatohepatitis or hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in liver and serum lipid parameters can be a predictor of disease development. 24 Kantartzis et al 25 in their study on 16 patients with fatty liver and 24 control subjects found that fatty liver was associated with decreased levels of high-density lipoprotein 2 (HDL 2 ) which is potent antiatherogenic. Moreover, in patients with NAFLD, abnormal serum ALT and AST are usually present when the disease progress to steatohepatitis or hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%